Mandated Evaluation: Integrating the Funder-Fundee Relationship into a Model of Evaluation Utilization - Fred Mayhew (The Evaluation Center at Western Michigan University, 2011)
Background:   Evaluation is a tool that can promote accountability and enhance organizational improvement.  For these reasons funding entities from government to foundations are increasingly relying on program evaluation as a key instrument to determine effectiveness and hold recipient organizations accountable.  What has ensued is an environment of increasing evaluation efforts, where findings often weigh heavily on future funding decisions.    Purpose:  The purpose of this article is to examine how the nature of the funder-fundee interorganizational relationship influences evaluation utilization by the fundee organization.  Within this context, attention is paid to the role the evaluator plays in the evaluation process and the skills needed to promote utilization.         Setting:  A statewide multi-tier public/private initiative addressing early childhood education. Intervention:  Not applicable. Research Design:  A model is designed to test the influence of the nature of the funder-fundee interorganizational relationship on factors associated with utilization, and ultimately on use itself. Data Collection and Analysis:  A survey was administered online and data analysis was conducted using principal components analysis (PCA) and structural equation modeling (SEM). Findings:  The results suggest that the funder-fundee relationship plays a critical role in the evaluation process, and consequently influences utilization.  However, the findings indicate that the relationship among the mediating factors is more complex than originally hypothesized. Keywords:  Evaluation utilization; collaboration; interorganizational relationships